Effectiveness of Using Game Techniques to Improve English Vocabulary Mastery in Elementary School: A Systematic Literature Review - Pratiwi, Yuliani; Maulina, Maulina; Nasrullah, Rahmat (Universitas Negeri Gorontalo, 2025)
Vocabulary mastery is a fundamental aspect in English learning, especially at the elementary school level. However, many students still experience difficulties in mastering vocabulary optimally due to learning methods that are less interesting and not appropriate to their age characteristics. This study uses a Systematic Literature Review (SLR) methodology to look into how well game tactics can help elementary school students improve their command of English vocabulary. A total of 50 articles published from 2020 to 2025 from various sources using publish or perish were collected and analyzed according to predetermined both inclusion and exclusion standars. The study’s findings indicate that game techniques have a favorable effect on enhancing vocabulary mastery, learning motivation, and active student engagement.Various types of games such as flash card, scrabble game, word game and wordwall have been demonstrated to be successful in aiding students in comprehending and rebember new vocabulary. However, there are also several obstacles such as limited time, facilities, and teachers' abilities in implementing game techniques optimally. The results of this investigation should be a reference for educators, researchers, and educational policy makers in developing more interesting and effective English learning methods at the elementary school level.